TRANSLATION ANALYSIS OF METAPHORSIN THE LOST SYMBOL NOVEL BY DAN BROWN - Fuji Nursyamsiah, - (2011)
This study is entitled TRANSLATION ANALYSIS OF METAPHORS IN THE LOST SYMBOL NOVEL BY DAN BROWN. The aims of the study are to discover the types of metaphors used in the novel, the procedures of translation applied by the translator and the quality of translation. By using a qualitative case method with textual comparison design, the data were collected through documents of the novels. Through a textual descriptive analysis, they were classified and analysed by using Knowles and Moon's theory of types of metaphor (2006), Newmark's theory concerning procedure of translation (1988) and Larson's theory concerning the criteria of good translation. The findings reveal that there are two types of metaphor which consist of conventional metaphor (55.75%) and creative metaphor (44.25%). The procedure mostly applied in translating the metaphors is literal (34.51%). Moreover, the quality of translation is generally acceptable, understandable and suitable despite a translation which is inaccurate. Most of the translations fulfil the criteria of a good translation. Thus, this study concludes that metaphor is translatability; it depends on the translator in choosing the appropriate procedure to translate the metaphor so the translated metaphor is suitable for the context of the source metaphor. Key terms: analysis, translation, metaphor, translation of metaphor, translation procedure.